Mechanically tunable PDMS-based polyHIPE acoustic materials. Issue 16 (30th March 2022) - McKenzie, Tucker J.; Rost, Kathryn; Smail, Soren; Mondain-Monval, Olivier; Brunet, Thomas; Ayres, Neil
Abstract : Porous PDMS elastomers were synthesized using emulsion templated thiol–ene "click" reactions to obtain materials with tunable storage moduli at a single porosity value that achieve low sound speed values of ∼40 m s −1 . Abstract : Polymer-based acoustic metamaterials possess properties including acoustic wave manipulation, cloaking, and sound dampening. Here, PDMS-based elastomers were prepared using thiol–ene "click reactions" with emulsion templating. Acoustic analysis showed these materials achieved sound speed values of ∼ 40 m s −1, close to the predicted minimum of ∼25 m s −1 attainable.